FAKTOR-FAKTOR YANG MEMPENGARUHI PELUANG PENCARI KERJA DALAM MENGAKSES INTERNET DI SUMATERA BARAT - Wiranti, Hilda; Satrianto, Alpon (Universitas Negeri Padang, 2020)
Abstract: This study aims to determine (1) the effect of the level of education on the opportunitiesfor job seekers to access the internet in West Sumatra. (2) the influence of gender on job seekers'opportunities to access the internet in West Sumatra. (3) the influence of age on the opportunitiesfor job seekers to access the internet in West Sumatra. (4) the influence of the area of residence onthe opportunities for job seekers to access the internet in West Sumatra. (5) the effect of income onjob search opportunities in accessing the internet in West Sumatra. This type of research isdescriptive - associative. The types and sources of data from the Socio-Economic Survey aresecondary. In this study using data that already exists in a data collection (National Socio-Economic Survey (SUSENAS) in 2018. The analysis tool used is logistic regression analysis, andthe total number of job seekers is 1,641 people. From the results of this study, it is explained that(1) education has a significant positive effect on the opportunities for job seekers to access theinternet in West Sumatra, (2) gender has no significant negative effect on the opportunities for jobseekers to access the internet in West Sumatra. (3) age has no significant positive effect on theopportunities for job seekers to access the internet in West Sumatra (4) the area of residence has apositive and significant effect on the opportunities for job seekers to access the internet in WestSumatra. (5) income has a significant positive effect on the opportunities for job seekers to accessthe internet in West Sumatra. As for the results of the research, so that the government of WestSumatra Province can provide socialization on the use of the internet in looking for work andbecome a consideration for the government in formulating a policy related to job availability forjob seekers in accessing the internet.Keywords: Job seekers, Internet, Logistic Regression.